Effect of sodium ascorbate and delayed treatment on the shear bond strength of composite resin to enamel following bleaching - TÜRKMEN, CAFER; YILMAZ ATALI, PINAR (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2016)
Background: The effect of bleaching on enamel surfaces, as well as exploring methods of preventing the weakening of bond strength of two different adhesives to bleached enamel surfaces. Objective: This study compared the shear bond strength (SBS) of two different adhesives on bleached enamel immediately after bleaching, with a 1-week delay, and following application of an antioxidizing agent after bleaching. Materilas and Method: The enamel surfaces of 140 incisors were divided into 14 groups. Two unbleached enamel groups (n = 20) were prepared as negative controls of the Adper Single Bond 2 total-etch and Clearfil Tri S Bond self-etch adhesives. The remaining surfaces were randomly divided into two bleaching groups treated with 35% Beyond Max (n = 60) and 38% Opalescence Xtra Boost (n = 60). Each bleaching group was then divided into two subgroups using the total and self-etch adhesive systems. Specimens were bonded immediately after bleaching, after treatment with 10% sodium ascorbate (SA) gel, or after 1-week of immersion in artificial saliva. All groups were restored with composite resin. After thermocycling, SBS was measured and data were analyzed. Results: In the control groups, there was no statistically-significant difference in SBS between self-and total-etch adhesives. Among all bleaching groups, no statistically-significant differences in SBS were noted, although the SA-treated delayed bonding (1-week) groups had the highest values. The lowest values were noted for the groups bonded immediately after bleaching.
Keywords: Antioxidant effect; bleaching agents; dental adhesives; dental enamel; shear bond strength; PEROXIDE; HYDROGEL